Economic effects of unemployment insurance for entrepreneurs in South Korea - Jiyeon Kim (KDI Journal of Economic Policy, 2024)
This paper aims to examine the economic impact of the implementation of an unemployment insurance (UI) program for entrepreneurs in South Korea. Despite facing labor market risks similar to paid employees, entrepreneurs are often not eligible for UI in many countries. South Korea, where entrepreneurs represent over 20% of the workforce, is considering a design of UI for entrepreneurs, with the goal of providing coverage to this group by 2025. This study examines how the addition of UI for entrepreneurs would impact the economy using a model of entrepreneurship based on a search and matching framework. The study's findings suggest that the implementation of UI for entrepreneurs would lead to increased business closures and reduced hiring, resulting in a slack labor market, which in turn would reduce social welfare overall. However, social welfare can be improved by subsidizing UI contributions paid by entrepreneurs, which provides the greatest improvement in social welfare compared to other social protection systems such as unemployment assistance.
Keywords: J68; L26; H53; E24; 330; Entrepreneurship; Unemployment Insurance; Search and matching